Primary Malignant Melanoma of the Breast: A Report of Two Cases - Jiwon Koh; Jihyeon Lee; So Youn Jung; Han Sung Kang; Tak Yun; Youngmee Kwon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Primary malignant melanoma of the breast (PMMB) is a rare tumor with only a few case reports available in the literature. We report two cases of PMMB, one derived from the breast parenchyma and the other from the breast skin. The first case consisted of atypical epithelioid cells without overt melanocytic differentiation like melanin pigments. The tumor cells showed diffuse positivity for S100 protein, tyrosinase, and BRAF V600E. However, the tumor cells were negative for cytokeratin, epithelial membrane antigen, and HMB-45. The second case showed atypical melanocytic proliferation with heavy melanin pigmentation. The tumor cells were positive for S100 protein, HMB-45, tyrosinase, and BRAF V600E. These two cases represent two distinct presentations of PMMB in terms of skin involvement, melanin pigmentation, and HMB-45 positivity. Although PMMB is very rare, the possibility of this entity should be considered in malignant epithelioid neoplasms in the breast parenchyma.